Isolasi Dan Karakterisasi Bakteri Asam Laktat Dari Susu Kuda Bima (Equus sp.) Yang Berpotensi Sebagai Probiotik - Suryani, Elsa Mega; Gaffar, Affan (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2024)
The aim of this research is to isolate and characterize lactic acid bacteria from mare's milk which have the potential to act as probiotics. Bacterial identification includes gram staining, antimicrobial activity test, hemolytic activity test, pH and bile salt tolerance test. The research results showed that C5 isolates isolated from horse milk samples had potential as probiotics. Characterization includes the form of bacillary bacteria, antimicrobial activity against the pathogenic bacteria Escherichia coli ATCC of 0.40 mm, gamma hemolysis, tolerance to pH 2, 3, 5 and tolerance to bile salts of 0.4-1%.